205k views
0 votes
Solve the system by elimination.
3x + 3 = 3y
2x - 6y = 2

User NTuply
by
6.4k points

2 Answers

6 votes

Answer:

(-2, -1)

Explanation:

both equation form: Ax + By = C

3x - 3y = -3 - 2×(3x - 3y = -3) = 6x + 6y = 6

2x - 6y = 2 - Terms opposite = 2x - 6y = 2

( Add) - 4x = 8

divide by -4 = x = -2

Put X value in equations 3(-2) + 3 = 3y and solve -

-6 + 3 = 3y

-3 = 3y

-1 = y

Answer= (-2, -1)

User Alok Gupta
by
6.3k points
5 votes

Answer:

The Point Form is: (-2,-1)

Equation form is x= -2, y = -1

Explanation:

User Tishawna
by
5.6k points